Evaluation of the effect of enamel preparation on retention rate of fissure sealant - Askarizadeh Nahid; Babaee G Zahra; Rezvani Yasaman (Wolters Kluwer Medknow Publications, 2012)
Background: Prevention from caries is a principle in dentistry and fissure sealant therapy is being used as a preventive method success of sealants is directly depending on their retention. Aim: The Aim of the present study is to evaluate effects of enamel preparation on sealant retention. Settings and Design: Clinical trial Materials and Methods: About 57 children aged 6-8 year old took part in this study. 200 first molar teeth of these children has been randomly separated into two groups: A case group (Mechanically preparation of enamel) and a control group (conventional method, without preparation). After applying fissure sealants children were followed up 6 months later. Statistical Analysis Used: Mann- U- Whitney Test was used. Results: Complete retention after 6 month follow up was 86.7% in case group and 82.8% in control group. No significant difference was seen between the groups after 6 month follow up. ( P = 0.508). Conclusion: Although statistical evaluation didn't show significant difference, but sealant retention was more after preparation technique.